Composite biological activated carbon for deodorization and preparation method thereof

By adding metal salts and composite microbial agents during the preparation of activated carbon, a composite biological activated carbon loaded with active components is generated, which solves the problem of insufficient adsorption capacity of existing activated carbon in removing odorous gases from toilets and farms, and achieves efficient removal of NH3 and H2S, while being environmentally friendly.

CN121466979APending Publication Date: 2026-02-06SHANXI XINHUA CHEM
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511775942.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-28
Publication Date
2026-02-06

AI Technical Summary

Technical Problem

Existing activated carbon has insufficient adsorption capacity and is difficult to remove low concentrations of NH3 and H2S odorous gases in toilets and farms simultaneously and efficiently. Furthermore, existing modification methods are complex and affect the effectiveness.

Method used

By adding metal salt solution and composite bacterial agent during the preparation of activated carbon, a composite biological activated carbon loaded with active components is prepared. The pore structure of activated carbon and the synergistic effect of biological strains are utilized to achieve efficient adsorption of NH3 and H2S.

Benefits of technology

The prepared composite bio-activated carbon generates a mesoporous and macroporous structure that is conducive to bacterial loading during the activation process, effectively removing NH3 and H2S. It is also environmentally friendly, requires no additional loading of active components, and significantly improves the adsorption effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of air purification, relates to an activated carbon technology, and discloses composite biological activated carbon for deodorization and a preparation method thereof.In the activated carbon preparation process, active components are added, the pore structure of the activated carbon is affected in the carbon activation process, and a mesopore-macropore structure beneficial to loading of composite strains is generated; the prepared activated carbon-loaded complex microbial inoculant decomposes stink components by utilizing biological action, effectively removes pollutants and is environment-friendly at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of air purification, and relates to activated carbon technology, in particular to a composite biological activated carbon for deodorization and a preparation method thereof. BACKGROUND

[0002] NH3 and H2S are two common odor gases with strong irritation and low odor threshold in toilet environment. A trace amount of them in the air environment can make people feel uncomfortable and cause various adverse physiological reactions, seriously affecting normal work and life. Activated carbon has been regarded as an effective adsorbent for odor substances, but its application has limitations. The binding force between activated carbon and gas molecules is weak, and gas molecules are easy to desorb from the adsorption surface. Physical and chemical modification is usually used to improve the adsorption capacity. Since NH3 and H2S belong to alkaline and acidic respectively, their physical and chemical properties are opposite, which seriously affects their simultaneous and efficient adsorption.

[0003] In "Preparation of Spherical Medium Control Carbon-based Adsorbent and Study on NH3 and H2S Low-temperature Removal Performance", Jiang Wuyou prepared an adsorbent with good adsorption performance for ammonia and hydrogen sulfide by loading binary active substances NiCl2 / CuO and NiCl2 / MgO on spherical mesoporous carbon. When the loading amount of NiCl2 is 15% and the loading amount of CuO is 20%, the hydrogen sulfide removal effect is 0.72 g / g, and the ammonia gas is 45.5 mg / g. Patent CN117414803A discloses a composite deodorizing activated carbon material which introduces a "composite microbial agent-plant essential oil-bubble gel" system. Microorganisms and plant essential oils are loaded on the pretreated activated carbon, and then mixed with bubble gel to press into shape, which greatly improves the adsorption effect and decomposition efficiency of odor.

[0004] In the above method, activated carbon acts as a carrier for adsorbing odor gases and providing a loading site and a reaction site for the loaded substances (metal active components, composite microbial agents), which plays a key role in the adsorption of odor gases.

[0005] The present application utilizes the simultaneous action of active species and biological bacteria and proposes a composite biological activated carbon for deodorization and a preparation method thereof. SUMMARY

[0006] The present application aims to provide a composite biological activated carbon for deodorization and a preparation method thereof, which can remove odor-causing gas pollutants such as NH3 and H2S in the environment and solve the problem of low-concentration NH3 and H2S removal in toilet and breeding environment.

[0007] The present application is implemented by using the following technical solutions: First, a preparation method of a composite biological activated carbon for deodorization includes the following steps: S1, preparing activated carbon Select porous carbon material with the required fineness and grind it; then add metal salt solution and mix; after mixing, add binder to prepare activated carbon particles with a particle size of 0.9-4 mm; after carbonization and activation, the preparation of activated carbon is completed. Based on the weight percentage of the porous carbon material taken, the metal salt solution is one or a mixture of two or more of the following: 1-40% Ni salt, 1-45% Cu salt, 1-25% Mg salt, 1-40% Fe salt, 1-40% Mn salt, 1-45% Zn salt, and 1-25% Mo salt. S2. Prepare compound bacterial agent solution Take a certain amount of activated carbon prepared in S1; prepare a compound bacterial agent solution according to 3-5 times the water volume of the activated carbon; Based on the weight percentage of activated carbon taken, the compound bacterial strains added to the compound bacterial agent solution are: Bacillus subtilis 3-15%, nitrifying bacteria 1-20%, denitrifying bacteria 1-20%, Lactobacillus plantarum 3-15%, ammonia-oxidizing bacteria 1-20%, and Bacillus licheniformis 3-15%. S3. Preparation of composite bioactivated carbon The activated carbon prepared in S1 is impregnated in the composite bacterial agent solution prepared in S2, filtered and dried to obtain composite biological activated carbon.

[0008] Furthermore, in step S1, the carbonization temperature of the activated carbon particles is 400~600℃, and the activation temperature is 800~900℃. The activation temperature cannot exceed 900℃ to prevent certain components from decomposing and losing their function.

[0009] Furthermore, in step S1, the porous carbon material is pulverized coal or carbon powder.

[0010] Furthermore, in step S1, the binder is one of tar, wood tar, cellulose, and starch.

[0011] Furthermore, in step S1, the activator used during activation is one or more of water vapor, CO2, and flue gas.

[0012] Furthermore, in step S1, the Ni salt is one or more of nickel chloride, nickel nitrate, nickel sulfate, nickel carbonate, and basic nickel carbonate. The Cu salt is one or more of copper chloride, copper nitrate, copper sulfate, copper carbonate, and basic copper carbonate; The Mg salt is one or more of magnesium chloride, magnesium nitrate, magnesium sulfate, and magnesium carbonate; The Fe salt is one or more of ferrous chloride, ferrous sulfate, ferrous carbonate, ferric chloride, ferric sulfate, ferric nitrate, and ferric citrate. The Mn salt is one or more of manganese chloride, manganese nitrate, manganese carbonate, and manganese sulfate; The Zn salt is one or more of zinc chloride, zinc nitrate, zinc sulfate, basic zinc carbonate; The Mo salt is one or more of ammonium molybdate, ammonium phosphomolybdate.

[0013] Further, step S3 is specifically: the activated carbon prepared in S1 is immersed in the composite microbial agent solution prepared in S2, oscillation is carried out at 20-35℃ for 1-10h, filtration is carried out, the activated carbon after immersion is dried at 35-40℃, and the composite bio-activated carbon is obtained.

[0014] Further, in step S1, the metal salt solution is a mixed solution of 18% nickel chloride and 25% copper sulfate by weight percentage; and the binder is a starch solution.

[0015] Further, in step S2, the composite microbial agent solution is a mixed solution of 5% bacillus subtilis, 20% nitrifying bacteria, 15% denitrifying bacteria, 8% lactobacillus plantarum, 15% ammonia-oxidizing bacteria and 8% bacillus licheniformis by weight percentage.

[0016] Second, a composite bio-activated carbon for deodorization is prepared by the preparation method described above.

[0017] Compared with the prior art, the present application has the following beneficial technical effects: 1. The present application combines the activated carbon loaded with active components and the composite microbial agent to jointly adsorb NH3 and H2S, and the active components are added in the preparation of activated carbon, without the need for loading the active components again.

[0018] 2. The addition of active components in the preparation of activated carbon has an influence on the pore structure of the activated carbon in the carbon activation process, and a mesopore structure beneficial to the loading of composite microbial species is generated; the prepared activated carbon loaded with the composite microbial agent decomposes the foul-smelling components by biological action, effectively removes the pollutants and is friendly to the environment. DETAILED DESCRIPTION

[0019] In order to more clearly understand the above-mentioned purposes, features and advantages of the present application, the schemes of the present application will be further described below. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.

[0020] In the following description, many specific details are set forth in order to provide a thorough understanding of the present application, but the present application can also be implemented in other different manners from those described herein; obviously, the embodiments in the description are only some embodiments of the present application, rather than all the embodiments.

[0021] The following is a detailed description of the specific embodiments of the present application.

[0022] First, a preparation method of a composite biological activated carbon for deodorization, comprising the following steps: S1, preparing activated carbon Selecting a porous carbon material with a desired fineness, grinding, and adding one or more of 1-40% Ni salt, 1-45% Cu salt, 1-25% Mg salt, 1-40% Fe salt, 1-40% Mn salt, 1-45% Zn salt, and 1-25% Mo salt in terms of weight percentage of the porous carbon material, and mixing uniformly; then adding a binder to prepare activated carbon particles with a particle size of 0.9-4 mm; carbonizing the activated carbon particles at a temperature of 400-600°C, and activating at a temperature of 800-900°C, and the activation temperature should not exceed 900°C to prevent decomposition of certain components and loss of function.

[0023] Further, the porous carbon material is coal powder or carbon powder (such as bamboo charcoal powder, charcoal powder, apricot kernel shell charcoal powder, peach shell charcoal powder, etc.).

[0024] Further, the activating agent used during activation is one or more of water vapor, CO2, and flue gas.

[0025] Further, the binder is one of tar, wood tar, cellulose, and starch.

[0026] Further, the Ni salt is one or more of nickel chloride, nickel nitrate, nickel sulfate, nickel carbonate, and basic nickel carbonate; the Cu salt is one or more of copper chloride, copper nitrate, copper sulfate, copper carbonate, and basic copper carbonate; the Mg salt is one or more of magnesium chloride, magnesium nitrate, magnesium sulfate, and magnesium carbonate; the Fe salt is one or more of ferrous chloride, ferrous sulfate, ferrous carbonate, ferric chloride, ferric sulfate, ferric nitrate, and ferric citrate; the Mn salt is one or more of manganese chloride, manganese nitrate, manganese carbonate, and manganese sulfate; the Zn salt is one or more of zinc chloride, zinc nitrate, zinc sulfate, and basic zinc carbonate; and the Mo salt is one or more of ammonium molybdate and phosphomolybdic acid ammonium.

[0027] S2, configuring a composite bacterial agent solution Pre-take a certain amount of activated carbon prepared in S1; configure a composite bacterial agent solution according to 3-5 times the water capacity of the activated carbon; According to the weight percentage of the activated carbon taken, the composite bacterial species added in the composite bacterial agent solution are 3-15% Bacillus subtilis, 1-20% nitrifying bacteria, 1-20% denitrifying bacteria, 3-15% Lactobacillus plantarum, 1-20% ammonia-oxidizing bacteria, and 3-15% Bacillus licheniformis; S3, preparing a composite biological activated carbon The activated carbon prepared in S1 is immersed in the composite microbial agent solution prepared in S2, oscillated at 20-35°C for 1-10h, filtered, and the immersed activated carbon is dried at 35-40°C to obtain the composite bio-activated carbon.

[0028] To verify the adsorption performance of the prepared composite bio-activated carbon on NH3 and H2S, the composite bio-activated carbon is prepared according to the above test scheme, and the adsorption performance of the composite bio-activated carbon on NH3 and H2S is tested according to the same test method. Example

[0029] 1) 1000g of coal powder of a certain fineness is ground, 20% of nickel chloride (200g), 15% of copper sulfate (150g), 8% of zinc chloride (80g), and 10% of ferric citrate (100g) are added according to the weight percentage, and a certain amount of tar is added as a binder to prepare columnar carbon particles with a particle size of 2mm. The particles are carbonized at 500°C and activated at 850°C to obtain activated carbon particles.

[0030] 2) 100g of the activated carbon prepared in step 1 is used to prepare a composite microbial agent with a water capacity of 3 times that of the activated carbon particles; the composite microbial agent contains 5% of Bacillus subtilis (5g), 10% of nitrifying bacteria (10g), 10% of denitrifying bacteria (10g), 3% of Lactobacillus plantarum (3g), 4% of ammonia-oxidizing bacteria (4g), and 3% of Bacillus licheniformis (3g) according to the weight percentage.

[0031] 3) 100g of the activated carbon prepared in step 1 is poured into the composite microbial agent solution prepared in step 2, oscillated at 25°C for 8h on a constant temperature oscillator, and the filtered activated carbon is dried at 35°C to obtain sample 1. Example

[0032] 1) 1000g of bamboo charcoal powder of a certain fineness is ground, 15% of nickel chloride (150g), 30% of copper sulfate (300g), 15% of zinc chloride (150g), 10% of magnesium chloride (100g), 18% of ferric nitrate (180g), 12% of manganese sulfate (120g), and 2% of ammonium molybdate (20g) are added according to the weight percentage, and a certain amount of wood tar is added as a binder to prepare columnar carbon particles with a particle size of 3mm. The particles are carbonized at 600°C and activated at 900°C to obtain activated carbon particles.

[0033] 2) 100g of the activated carbon prepared in step 1 is used to prepare a composite microbial agent with a water capacity of 3 times that of the activated carbon particles; the composite microbial agent contains 3% of Bacillus subtilis (3g), 15% of nitrifying bacteria (15g), 15% of denitrifying bacteria (15g), 7% of Lactobacillus plantarum (7g), 12% of ammonia-oxidizing bacteria (12g), and 6% of Bacillus licheniformis (6g) according to the weight percentage.

[0034] 3) Put 100g of activated carbon prepared in step 1 into the composite microbial agent solution prepared in step 2, and oscillate in a constant temperature oscillator at 30°C for 7h. The filtered activated carbon is dried at 38°C to obtain sample 2. Example 1

[0035] 1) Grind 1000g of bamboo charcoal powder to a certain fineness, add 18% nickel chloride (180g) and 25% copper sulfate (250g) according to the weight percentage, and add a certain amount of starch solution as a binder to prepare columnar carbon particles with a particle size of 3mm. The particles are carbonized at 650°C and activated at 800°C to obtain activated carbon particles.

[0036] 2) Take 100g of activated carbon prepared in step 1 and prepare a composite microbial agent according to 3 times the water capacity of the activated carbon particles; add Bacillus subtilis 5% (5g), nitrifying bacteria 20% (20g), denitrifying bacteria 15% (15g), Lactobacillus plantarum 8% (8g), ammonia-oxidizing bacteria 15% (15g), and Bacillus licheniformis 8% (8g) according to the weight percentage.

[0037] 3) Put 100g of activated carbon prepared in step 1 into the composite microbial agent solution prepared in step 2, and oscillate in a constant temperature oscillator at 35°C for 6h. The filtered activated carbon is dried at 40°C to obtain sample 3. Example 2

[0038] 1) Grind 1000g of coal powder to a certain fineness, add 30% nickel chloride (300g) according to the weight percentage, and add a certain amount of tar as a binder to prepare columnar carbon particles with a particle size of 2mm. The particles are carbonized at 500°C and activated at 850°C to obtain activated carbon particles.

[0039] 2) Take 100g of activated carbon prepared in step 1 and prepare a composite microbial agent according to 3 times the water capacity of the activated carbon particles; add Bacillus subtilis 7% (7g), nitrifying bacteria 15% (15g), denitrifying bacteria 20% (20g), Lactobacillus plantarum 10% (10g), ammonia-oxidizing bacteria 8% (8g), and Bacillus licheniformis 10% (10g) according to the weight percentage.

[0040] 3) Put 100g of activated carbon prepared in step 1 into the composite microbial agent solution prepared in step 2, and oscillate in a constant temperature oscillator at 35°C for 9h. The filtered activated carbon is dried at 38°C to obtain sample 4. Example 3

[0041] 1) Grind 1000g of coal powder to a certain fineness, add 28% copper sulfate (280g) according to the weight percentage, and add a certain amount of tar as a binder to prepare columnar carbon particles with a particle size of 4mm. The particles are carbonized at 500°C and activated at 900°C to obtain activated carbon particles.

[0042] 2) 100 g of the activated carbon prepared in step 1 was added to the composite microbial agent prepared in step 2 according to 3 times the water capacity of the activated carbon particles; the composite microbial agent was added with Bacillus subtilis 3% (3 g), nitrifying bacteria 18% (18 g), denitrifying bacteria 18% (18 g), Lactobacillus plantarum 3% (3 g), ammonia-oxidizing bacteria 15% (15 g), and Bacillus licheniformis 10% (10 g) according to the weight percentage.

[0043] 3) 100 g of the activated carbon prepared in step 1 was poured into the composite microbial agent solution prepared in step 2, and oscillated in a constant-temperature oscillator at 35°C for 3 h; the filtered activated carbon was dried at 40°C to obtain sample 5.

[0044] The deodorizing composite biological activated carbon of samples 1-5 was prepared by the above preparation method.

[0045] Samples 1-5 were crushed into the same particle size, and packed into a power tube with a diameter of 2 mm according to the same test method; the test was carried out under the test conditions of NH3 initial concentration 1000 ppm, H2S initial concentration 1000 ppm, and gas specific speed 0.25 L / min·cm 2 The test results are shown in the following table.

[0046]

[0047] The activated carbon loaded with the composite microbial agent prepared by adding the active component in the preparation process has good adsorption performance on NH3 and H2S. According to the test results, the prepared composite biological activated carbon can simultaneously and effectively adsorb NH3 and H2S, but the adsorption effect also has certain differences, which is related to the pore structure of the prepared activated carbon, the loaded active component and the composite microbial agent. The researchers can also realize different adsorption effects of the composite biological activated carbon on NH3 and H2S by adjusting the pore structure, the active component and the composite microbial agent.

[0048] The above is only a specific embodiment of the present application, which enables those skilled in the art to understand or implement the present application. Although the foregoing embodiments are described in detail, those skilled in the art should understand that the technical solutions recorded in the foregoing embodiments can be modified, or some or all of the technical features can be replaced by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments, and they should be covered in the protection scope of the claims.

Claims

1. A method for preparing a composite type bio-activated carbon for deodorization, characterized by comprising the steps of: It comprises the following steps: ​ S1, preparing activated carbon Select the desired fineness of porous carbon material, and after grinding, add metal salt solution for mixing, add binder after mixing, and prepare activated carbon particles with a particle size of 0.9-4mm; After carbonization and activation, the preparation of activated carbon is completed; According to the weight percentage of the selected porous carbon material, the metal salt solution is one or more of 1-40% Ni salt, 1-45% Cu salt, 1-25% Mg salt, 1-40% Fe salt, 1-40% Mn salt, 1-45% Zn salt, 1-25% Mo salt and mixed solution of two or more; S2, configure composite microbial agent solution Pre-take a certain amount of activated carbon prepared in S1; Configure the composite microbial agent solution according to 3-5 times the water capacity of the activated carbon; According to the weight percentage of the selected activated carbon, the composite microbial species added in the composite microbial agent solution are 3-15% Bacillus subtilis, 1-20% nitrifying bacteria, 1-20% denitrifying bacteria, 3-15% Lactobacillus plantarum, 1-20% ammonia-oxidizing bacteria, and 3-15% Bacillus licheniformis. S3, preparing composite bio-activated carbon Immerse the activated carbon prepared in S1 in the composite microbial agent solution prepared in S2, filter and dry to obtain the composite bio-activated carbon.

2. The method of claim 1, wherein the method is characterized by: In step S1, the carbonization temperature of the activated carbon particles is 400-600℃, and the activation temperature is 800-900℃.

3. The method of claim 2, wherein the method is characterized by: In step S1, the porous carbon material is coal powder or carbon powder.

4. The method of claim 3, wherein the method is characterized by: In step S1, the binder is one of tar, wood tar, cellulose, and starch.

5. The method of claim 4, wherein the method is characterized by: In step S1, the activation agent uses one or more of water vapor, CO2, and flue gas.

6. The method of claim 1 or 5, wherein the preparation method of the composite bio-activated carbon for deodorization is characterized by: The Ni salt is one or more of nickel chloride, nickel nitrate, nickel sulfate, nickel carbonate, and basic nickel carbonate; The Cu salt is one or more of copper chloride, copper nitrate, copper sulfate, copper carbonate, and basic copper carbonate; The Mg salt is one or more of magnesium chloride, magnesium nitrate, magnesium sulfate, and magnesium carbonate; The Fe salt is one or more of ferrous chloride, ferrous sulfate, ferrous carbonate, ferric chloride, ferric sulfate, ferric nitrate, and ferric citrate; The Mn salt is one or more of manganese chloride, manganese nitrate, manganese carbonate, and manganese sulfate; The Zn salt is one or more of zinc chloride, zinc nitrate, zinc sulfate, and basic zinc carbonate; The Mo salt is one or more of ammonium molybdate and phosphomolybdic acid ammonium.

7. The method of claim 6, wherein the method is characterized by: Step S3 is: immerse the activated carbon prepared in S1 in the composite microbial agent solution prepared in S2, oscillate at a temperature of 20-35℃ for 1-10h, filter, dry the immersed activated carbon at 35-40℃, and obtain the composite bio-activated carbon.

8. The method of claim 7, wherein the method is characterized by: In step S1, the metal salt solution is a mixed solution of 18% nickel chloride and 25% copper sulfate by weight; The binder is a starch solution.

9. The method of claim 8, wherein the method is characterized by: In step S2, the composite microbial agent solution is a mixed solution of 5% Bacillus subtilis, 20% nitrifying bacteria, 15% denitrifying bacteria, 8% Lactobacillus plantarum, 15% ammonia-oxidizing bacteria, and 8% Bacillus licheniformis by weight percentage.

10. A composite type bio-activated carbon for deodorization, characterized by comprising: a porous carrier; a microorganism immobilized on the porous carrier; and a biodegradable polymer. Prepared by the preparation method of any one of claims 1-9.

Citation Information

Patent Citations

  • Composite deodorization activated carbon material as well as preparation method and application thereof

    CN117414803A